Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1103/physrevd.86.114039
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive gauge bosons production beyond QCD factorization

Abstract: We discuss single diffractive gauge boson ð Ã ; W AE ; ZÞ production in proton-proton collisions at different (Large Hadron Collider and Relativistic Heavy Ion Collider) energies within the color dipole approach. The calculations are performed for gauge bosons produced at forward rapidities. The diffractive cross section is predicted as a function of the fractional momentum and invariant mass of the lepton pair. We found a dramatic breakdown of the diffractive QCD factorization caused by an interplay of hard a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 44 publications
(87 reference statements)
1
53
0
Order By: Relevance
“…Abelian diffractive radiation of any particle is described by the same Feynman graphs, only couplings and spin structure are different [15]. In Fig.…”
Section: Diffractive Z and W Productionmentioning
confidence: 99%
“…Abelian diffractive radiation of any particle is described by the same Feynman graphs, only couplings and spin structure are different [15]. In Fig.…”
Section: Diffractive Z and W Productionmentioning
confidence: 99%
“…Recently, in Refs. [11,16,33] it was explicitly shown that factorisation in diffractive Abelian radiation is therefore even more broken due to presence of spectator partons in the colliding hadrons. Besides, the saturated shape of the dipole cross section (3), therefore, leads to several unusual features of diffractive DY cross section.…”
Section: Diffractive Abelian Radiationmentioning
confidence: 99%
“…In general, diffractive radiation of any Abelian particle is given by the same graphs as the diffractive DY process, with an appropriate use of couplings and spin structure [33]. In Fig.…”
Section: Diffractive Abelian Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a process, the invariant mass of the lepton pair can easily be reconstructed and, depending on experimental capabilities, pushed to rather low values, allowing a detailed characterisation of the hard-scale dependence of the suppression factor. Although estimates of the latter are present in the literature for the specific process at hand [27][28][29], we take a conservative approach and avoid to introduce any suppression factor. We further assume factorisation to hold and adopt factorised expressions for the relevant cross sections.…”
Section: Introductionmentioning
confidence: 99%